2012
DOI: 10.1038/modpathol.2011.201
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of HER2 status determination on breast core-needle biopsies (immunohistochemistry, FISH, CISH and SISH vs FISH)

Abstract: Preoperative breast cancer diagnosis on core biopsies has become a standard of care in many countries. Controversies exist concerning the accuracy of HER2 testing on biopsies as compared with surgical specimens, and few data exist concerning the use of emerging technologies such as bright-field in-situ hybridization in such a setting. A French multicenter, cross-sectional, histopathological study assessed the concordance of HER2 status determined by immunohistochemistry and silver (SISH) or chromogenic in-situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 32 publications
1
36
0
Order By: Relevance
“…Concordance between IHC and ISH technologies in HER2 status assessment in breast cancer has been the subject of several previous studies [3], [6], [18], [19]. These studies confirmed a realistic concordance between IHC and SISH technology, especially in settings where ISH is applied as reflex testing in IHC score 2+ cases.…”
Section: Discussionsupporting
confidence: 57%
“…Concordance between IHC and ISH technologies in HER2 status assessment in breast cancer has been the subject of several previous studies [3], [6], [18], [19]. These studies confirmed a realistic concordance between IHC and SISH technology, especially in settings where ISH is applied as reflex testing in IHC score 2+ cases.…”
Section: Discussionsupporting
confidence: 57%
“…A previous publication including a subset of this study population, showed an overall concordance of 80 % between TMAs and whole sections for IHC assessment of ER, PR, and HER2, and notably the prognostic value of these markers was similar irrespective of assessment based on TMA or whole sections [36]. This study is predominantly based on SISH regarding HER2 status with an anticipated high accuracy compared to IHC [37]. Breast conserving surgery represents the surgical intervention predominantly used in our cohort.…”
Section: Discussionmentioning
confidence: 73%
“…Pre-analytic factors affect the test results less than immunohistochemistry. Nevertheless, the FISH technique is more expensive, it necessitates special equipment and educated personnel, its application process lasts longer, and a fluorescent microscope is required for the evaluation of the test (Francis et al, 2009;Papouchado et al, 2010;Ying et al, 2010;Arnould et al, 2012;Schiavon et al, 2012). The SISH method, which can be an alternative to the FISH technique, is comprised of a multimer technology, combined with enzyme metallography, which allows for the identification of the HER2 oncogene amplification with silver marking.…”
Section: Discussionmentioning
confidence: 99%